Increasing software development efficiency and maintainability for complex industrial systems – A case study. Issue 3 (3rd November 2011) - Lagerström, Robert; Sporrong, Ulf; Wall, Anders
SUMMARY It is difficult to manage complex software systems. Thus, many research initiatives focus on how to improve software development efficiency and maintainability. However, the trend in the industry is still alarming, software development projects fail, and maintenance is becoming more and more expensive. One problem could be that research has been focusing on the wrong things. Most research publications address either process improvements or architectural improvements. There are few known approaches that consider how architectural changes affect processes and vice versa. One method proposed, called the Business–Architecture–Process method, takes these aspects into consideration. In 2007 the method was tested in one case study. Findings in the 2007 case study show that the method is useful, but in need of improvements and further validation. The present paper employs the method in a second case study. The contribution in this paper is thus a second test and validation of the proposed method, and useful method improvements for future use of the method. Copyright © 2011 John Wiley & Sons, Ltd.